The Use of Business Intelligence to Support Strategic Decision Making in Digital Retail Companies in Indonesia - Soelistianto, Farida Arinie; Sono, Mohammad Gifari (Westscience Press, 2025)
This study explores the role of Business Intelligence (BI) in supporting strategic decision-making within digital retail companies in Indonesia. In an increasingly competitive digital retail environment, BI enables managers to transform raw data into actionable insights for informed decision-making. Using a qualitative approach, in-depth interviews were conducted with five informants, including managers and decision-makers from various digital retail companies. The findings reveal that BI enhances decision quality, provides operational efficiency, and supports proactive strategies by offering accurate, real-time information on customer behavior, market trends, and business performance. However, challenges such as system complexity, data integration issues, and limited analytical skills pose barriers to effective BI utilization. This study contributes to a deeper understanding of BI implementation in the Indonesian digital retail sector and offers practical insights for managers aiming to leverage BI for strategic advantage.